Comparison of electrical characteristics between atrial and ventricular side His-bundle pacing in bradycardia patients. (25th November 2020) - Liu, X; Gu, M; Hu, Y.R; Hua, W; Zhang, S
Abstract: Background: His-bundle pacing (HBP) is recognized as the most physiological way of pacing but with less study focused on electrical characteristics in different site. Purpose: We aimed to evaluate the differences of pacing and echocardiographic parameters between atrial and ventricular side His-bundle pacing. Methods: Patients who successfully underwent HBP implantation from September 2018 to August 2019 were retrospectively analyzed. All patients were assigned to atrial-side HBP (aHBP) group or ventricular-side HBP (vHBP) group according to the location of the His-bundle pacing lead, which was confirmed by two methods including postoperative echocardiography and visualization of tricuspid valve annulus (TVA). The pacing and echocardiographic parameters were compared between two groups during the procedure and at 3-month follow-up. Results: A total of 71 bradycardia patients who successfully underwent HBP implantation and confirmed lead position were included. Among them, twenty-seven were assigned to aHBP group and the other 44 were assigned to vHBP group with no significant differences in baseline clinical characteristics between two groups. During the procedure, the proportion of selective HBP was significantly higher (77.8% vs. 11.4%; P<0.01) and the intra-procedural HV intervals was significantly longer (50.85±6.53 ms vs. 42.95±6.02 ms, P<0.01) in aHBP group than in vHBP group. The capture threshold in vHBP group was significantly lower than in aHBP group at implantation (0.92±0.22 V/1.0ms vs. 1.05±0.26 V/1.0ms, P=0.03) and remain significantly difference after 3-month follow-up (0.98±0.23 V/1.0ms vs. 1.15±0.44 V/1.0ms, P=0.03). The R-wave amplitude was significantly higher in vHBP group than in aHBP group at implantation (5.82±2.52 mV vs. 3.74±1.81 mV, P<0.01), and these differences still persisted during follow-up (5.88±2.51 mV vs. 3.67±1.61 mV, P<0.01). During 3-month follow-up, an increase in the capture threshold >1 V/1.0ms was seen in 2 cases in aHBP group while all patients remained stable in vHBP group. One patient developed a pocket hematoma in aHBP group compared to none in vHBP group. None of deterioration of tricuspid regurgitation and other procedure-related complications were observed during 3-month follow-up. Conclusions: Ventricular side His-bundle pacing can achieve favourable pacing parameters including a lower pacing threshold and a higher R-wave amplitude than atrial side His-bundle pacing, which may be an ideal pacing strategy for patients in need of ventricular pacing. Funding Acknowledgement: Type of funding source: None